IDNLearn.com provides a collaborative environment for finding and sharing answers. Get prompt and accurate answers to your questions from our community of experts who are always ready to help.

Inverse equation

1. g(n)= 2+(n+2)^3
2. f(n)= 1/2n+3/2






Sagot :

Answer:

1

[tex]g(n) = 2 + {(n + 2)}^{3} [/tex]

let the inverse be m :

[tex]m = 2 + {(n + 2)}^{3} \\ {(n + 2)}^{3} = m - 2 \\ n + 2 = \sqrt[3]{(m - 2)} \\ n = \{ \sqrt[ 3]{(m - 2)} - 2 \}[/tex]

therefore:

[tex]{ \boxed{ \boxed{g {}^{ - 1}(n) = \{ \sqrt[3]{(n - 2)} - 2 \}}}}[/tex]

2.

[tex]f(n) = \frac{1}{2} n + \frac{3}{2} [/tex]

let inverse be x :

[tex]x = \frac{1}{2} n + \frac{3}{2} \\ \\ 2x = n + 3 \\ n = 2x - 3[/tex]

therefore:

[tex]{ \boxed{ \boxed{f {}^{ - 1}(n) = 2n - 3 }}}[/tex]

We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Thank you for choosing IDNLearn.com. We’re here to provide reliable answers, so please visit us again for more solutions.